Соціальна роль освіти і знання у глобалізованому світі (до питання про корпаративну освіту) - Давидов, П. Г.; Саранов, В. В. (НТУ "ХПІ", 2015)
У статті розглядається роль освіти в сучасному глобалізованому світі. Аналізується роль державної і корпоративної освіти у економічному зростанні України. Досліджується вплив знань і освіти та шляхи формування «людського капіталу» і суспільства знань у нашій державі.

The article discusses the role of education in today's globalized world. The role of public and corporate education in economic growth in Ukraine. We investigate the influence of knowledge and education and the way of formation of "human capital" and the knowledge society in our country.
The social role of education and knowledge in a globalized world (the question of corporate entities)
Keywords: суспільство знань; глобалізація; інформація; людський капітал; corporate education; knowledge society; globalization; information